Characteristics of smart cities and transformation requirements - Jabor, Entezar Jassem; Jassim, Shurooq Naeem (Al-Adab Journal, 2019)
Smart City is the city where advanced communications and information technology services are available. It relies on the idea of connecting public places in the city such as airports, markets, parks, parks, hospitals and public gathering places in the city through the use of advanced communication technologies such as WiMAX technology and hotspots, so that the residents of the smart city can use their mobile devices and sufficient access to the global network Information (Internet) and communication with all institutions and bodies in their city to carry out their work electronically. The term Smart City was launched in 1994, specifically in Europe, and spread in most cities of the world, and has been applied in various parts of the world, and there are smart cities in Europe, America, Asia and Australia, and there were models of global smart cities such as Helsinki in Finland. The research aims to demonstrate the concept of smart cities and the characteristics of these cities and the requirements of the transition towards smart cities, so the research posed the following problem: Are smart cities have certain characteristics? And what are these characteristics? What are the requirements to achieve smart cities? The research focused on smart cities and their characteristics due to the lack of studies and urban contributions to the study of smart cities and their requirements, especially with regard to the information and technical aspect and its importance in the management of cities and provide services to the population.